Frequency of IFNγ-producing T cells correlates with seroreactivity and activated T cells during canine Trypanosoma cruzi infection - Hartley, Ashley N. (2014)
Vaccines to prevent Trypanosoma cruzi infection in humans or animals are not available, and in many settings, dogs are an important source of domestic infection for the insect vector. Identification of infected canines is crucial for evaluating peridomestic transmission dynamics and parasite control strategies. As immune control of T. cruzi infection is dependent on humoral and cell-mediated immune responses, we aimed to define a serodiagnostic assay and T cell phenotypic markers for identifying infected dogs and studying the canine T. cruzi-specific immune response. Plasma samples and peripheral blood mononuclear cells (PBMCs) were obtained from forty-two dogs living in a T. cruzi-endemic region. Twenty dogs were known to be seropositive and nine seronegative by conventional serologic tests two years prior to our study. To determine canine seroreactivity, we tested sera or plasma samples in a multiplex bead array against eleven recombinant T. cruzi proteins. Ninety-four percent (17/18) of dogs positive by multiplex serology were initially positive by conventional serology. The frequency of IFNγ-producing cells in PBMCs responding to T. cruzi correlated to serological status, identifying 95% of multiplex seropositive dogs. Intracellular staining identified CD4§ssup§+§ esup§ and CD8§ssup§+§esup§ T cell populations as the sources of T. cruzi lysate-induced IFNγ. Low expression of CCR7 and CD62L on CD4§ssup§+§esup§ and CD8§ssup§+§esup§ T cells suggested a predominance of effector/effector memory T cells in seropositive canines. These results are the first, to our knowledge, to correlate T. cruzi-specific antibody responses with T cell responses in naturally infected dogs and validate these methods for identifying dogs exposed to T. cruzi.